Labour taxation and shock propagation in a New Keynesian model with search frictions - Juuso Vanhala (Bank of Finland, 2006)
This paper studies the implications of labour taxation in determining the sensitivity of an economy to macroeconomic shocks. We construct a New Keynesian business cycle model with matching frictions of the labour market, where sluggish employment adjustment implies a key role for labour markets in determining shock propagation.We consider three policy instruments to analyze the steady state and dynamic effects of tax reforms: the marginal tax rate and replacement ratio amplify shock responses whereas employment subsidies weaken them.The tax instruments affect the degree to which the wage absorbs shocks.We show that the relative effects of the tax instruments and thus the effects of tax progression are sensitive to the initial degree of tax progression in the economy.Increasing tax progression when taxation is initially progressive is harmful for steady state employment and output, and amplifies the sensitivity of macroeconomic variables to shocks.When taxation is initially proportional, increasing progression is beneficial for output and employment and dampens shock responses of macroeconomic variables.
URN:NBN:fi:bof-20140807414
Keywords: J64; E24; E32; 330; matching; income taxation; business cycles